Fingerprint profiling for quality evaluation and the related biological activity analysis of polysaccharides from Liuweizhiji Gegen-Sangshen beverage - Wei, Shulin; Li, Mingxing; Zhao, Long; Wang, Tiangang; Wu, Ke; Yang, Jiayue; Tang, Mingyun; Zhao, Yueshui; Shen, Jing; Du, Fukuan; Chen, Yu; Deng, Shuai; et al. (Frontiers in Nutrition, 2024)
Liuweizhiji Gegen-Sangshen beverage (LGS) is popular in China, which has been used for alleviating alcohol-mediated discomfort and preventing alcoholic liver disease (ALD). This beverage is consisted of six herbal components that are known as functional foods and fruits. LGS is rich in polysaccharides, however, the activity and quality evaluation of LGS-derived polysaccharides remain unexplored. The purpose of this study is thus to establish a comprehensive quality control methodology for the assessment of LGS polysaccharides (LGSP) and to further explore the anti-oxidant, anti-inflammatory as well as prebiotic effect of LGSP. LGSP was extracted, followed by analysis of molecular weight distribution, monosaccharide content and structural characterization via integrating the application of high-performance size exclusion chromatography (HPSEC), 1-phenyl-3-methyl-5-pyrazolone-HPLC (PMP-HPLC), fourier transform infrared spectroscopy (FT-IR) as well as nuclear magnetic resonance spectroscopy (NMR) techniques. The results demonstrated that LGSP had two molecular weight distribution peaks, with the average molecular weights of (6.569 ± 0.12) × 10^4 Da and (4.641 ± 0.30) × 10^4 Da. LGSP was composed of 8 monosaccharides, with galacturonic acid, glucose rhamnose and galactose representing the highest molar ratios. Homogalacturonic acid (HG) type and rhamnosegalacturonic acid glycans I (RG-I) type and α-1,4-glucan were present inLGSP. LGSP concentration in LGS was 17.94 ± 0.28 mg/mL. Furthermore, fingerprint analysis combined with composition quantification of 10 batches of LGSP demonstrated that there was a high similarity among batches. Notably, LGSP exhibited anti-oxidant effect and inhibited expressions of pro-inflammatory factors (TNF-α and IL-6) in LPS-stimulated RAW 264.7 cells. In addition, LGSP remarkably promoted the proliferation of probiotics Lactobacillus, Bifidobacterium bifidum and Bifidobacterium adolescentis, showing good prebiotic activity. The results of present study would be of help to gain the understanding of structure-activity relationship ofLGSP, provide a reference for quality evaluation of bioactive LGSP, and facilitate development of unique health and functional products in the future.